Is Tax Morale the Most Important Factor Affecting Tax Compliance Behavior of Vietnamese Small and Medium Enterprises? - Thao, Le Thi; Lan, Le Thi (Archives of Business Research, 2025)
This study provides a comprehensive overview of the factors affecting the Tax compliance behavior of Vietnamese small and medium enterprises, through a case study of enterprises in Thanh Hoa City. From the model building and analysis of factors affecting the Tax compliance behavior of small and medium enterprises, the study quantified the level of influence of the moderating variable Tax knowledge. From the research results, the author will propose some recommendations to improve Tax compliance behavior in the coming time. This study uses the perspective of enterprises through stratified random sampling, collecting and analyzing survey data from 290 small and medium enterprises in Thanh Hoa city using smart 3.0 software. Structural equation modeling (SEM) was established to quantify the impact of 11 influencing factors and 1 moderating variable on Tax compliance behavior of small and medium enterprises. The research results show that Tax morality has the strongest impact on Tax compliance behavior and Tax morality has a moderating effect on Tax compliance behavior by Tax knowledge. This shows the importance of attitudes, ethical values and perceptions of enterprises towards tax obligations, and emphasizes that Tax knowledge plays an important role in improving Tax morality and promoting Tax compliance. In addition, the factors Auditability, Social Norms, Fine, Tax compliance cost, Trust in tax authorities play an important role in determining the Tax compliance behavior of small and medium enterprises in Thanh Hoa city. This study has important implications both theoretically and practically, especially in the context of small and medium enterprises playing an important role in the Vietnamese economy. The study clarifies the role of factors related to enterprises' attitudes and perceptions in Tax compliance. Finally, this study seeks to contribute to the broader academic discourse on corporate tax compliance by providing empirical evidence from the Vietnamese context, which can be applied to other developing economies with similar socio-economic structures.